2021
DOI: 10.3390/pr9040599
|View full text |Cite
|
Sign up to set email alerts
|

MINLP Model for Operational Optimization of LNG Terminals

Abstract: Liquefied natural gas (LNG) is a clear and promising fossil fuel which emits less greenhouse gas (GHG) and has almost no environmentally damaging sulfur dioxide compared with other fossil fuels. An LNG import terminal is a facility that regasifies LNG into natural gas, which is supplied to industrial and residential users. Modeling and optimization of the LNG terminals may reduce energy consumption and GHG emission. A mixed-integer nonlinear programming model of the LNG terminal is developed to minimize the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The comprehensiveness level of services C s at the transshipment terminal is assessed by comparing a cardinality of a set of services ordered by a customer (Equation ( 9)) with a cardinality of a set of services available at a certain terminal (Equation ( 10))-this comparison is given here as Equation (11).…”
Section: Calculation Of the Level Of Comprehensiveness Of Servicementioning
confidence: 99%
See 1 more Smart Citation
“…The comprehensiveness level of services C s at the transshipment terminal is assessed by comparing a cardinality of a set of services ordered by a customer (Equation ( 9)) with a cardinality of a set of services available at a certain terminal (Equation ( 10))-this comparison is given here as Equation (11).…”
Section: Calculation Of the Level Of Comprehensiveness Of Servicementioning
confidence: 99%
“…Various researchers have investigated sustainable energy issues and have discovered methods for reducing energy consumption. For example, Ye et al [11] suggested that liquefied natural gas import terminals can reduce energy consumption by cold energy recovery of the gas or a boil-off gas handling process. Energy reduction led Alzahrani et al [12] to review methods for the decarbonization of seaports (seaports are infrastructure facilities that conduct transshipment processes as well), which also can lead to a reduction in energy waste.…”
Section: Introductionmentioning
confidence: 99%
“…Being liquefied, natural gas (LNG) is 600 times smaller than the gaseous state of N.G., LNG becomes especially attractive if obtained at a competitive cost. The authors of this article, Liang Zhao et al [8], show that modeling and optimizing the LNG terminals may also reduce energy consumption and GHG emissions. In this work, the authors propose an operational optimization model of the LNG terminal to minimize the energy consumption of boil-off gas (BOG) compressors and low pressure (L.P.) pumps.…”
Section: Original Researchmentioning
confidence: 99%
“…(1) WOA is applied to the position deployment optimization of mobile conventional missiles. It overcomes the disadvantages of many constraints and difficult to solve the position deployment optimization problem and provides a new method for solving the problem (2) A three-level sector position deployment model and a position optimization model based on MINLP [23] are established. The deployment mode is more complex, and the constraint conditions of the model are more complete, which is more in line with the actual combat of conventional missile weapons…”
Section: Introductionmentioning
confidence: 99%